Exploration on Foreign Exchange Transaction Tax: Tobin Tax and Spahn Tax - Lei, Heng (2013)
In 1970s, James Tobin proposed the introduction of a transaction tax on the foreign exchange market, the so-called Tobin tax, to deal with exchange rate volatility. Then in 1990s, Paul Bernd Spahn suggested a two-tier Tobin tax. In spite that transaction tax is being frequently discussed by both economists and policy makers, neither of the Tobin tax nor Spahn tax has ever been imposed. Investigation on the consequences of the introduction of a Tobin tax and a Spahn tax on an asset market model are conducted by the means of laboratory experiments. Basically, there are three treatments: one is the Smith, Suchanek and Williams (1998) treatment (SSW), one is Tobin treatment in which a Tobin tax is imposed, and the last one is Spahn treatment where a Spahn tax is levied. The main results are: (i) neither Tobin nor Spahn tax reduces bubbles significantly. But Spahn tax curbs market volatility. A transaction tax, Tobin tax or Spahn tax, would not monotonously modify bubbles or volatility, while some specific tax rates contribute to a market with few bubbles and low volatility. (ii) When analyzed results of different phases, Tobin tax is preferred to Spahn tax. (iii) Spahn tax always generates more tax revenues than Tobin tax. (iv) Both Tobin tax and Spahn tax hamper the equality of wealth distribution.